2011
DOI: 10.1364/ao.50.003201
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz reflectivities of metal-coated mirrors

Abstract: Terahertz (THz) reflectivities of a variety of metal-coated mirrors were measured. Gold, silver, and aluminum coatings were tested and compared. It was found that all types of optical metal-coated mirrors perform equally well as THz reflectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…The reflectivity of a metal surface is near unity in the 0.1-10 THz band due to high electrical conductivity. Thus, well-polished metal surfaces or metal coating mirrors could act as THz reflectors [31,32]. The most commonly used metals for this purpose are gold, silver, copper and aluminum.…”
Section: Pipe Casing Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reflectivity of a metal surface is near unity in the 0.1-10 THz band due to high electrical conductivity. Thus, well-polished metal surfaces or metal coating mirrors could act as THz reflectors [31,32]. The most commonly used metals for this purpose are gold, silver, copper and aluminum.…”
Section: Pipe Casing Materialsmentioning
confidence: 99%
“…The thickness of a metal or metal coating should also be taken into account. In order to achieve maximum reflectivity for a given metal, the thickness of the metal layer must be at least two penetration depths, δ at the frequency of the incident beam [32]. Penetration depth is the attenuation length of exponentially decaying electromagnetic field when the wave is incident on a conductor, that is,…”
Section: Pipe Casing Materialsmentioning
confidence: 99%
“…The resistivity of gold at room temperature is 2.271 × 10 −2 µΩm and the wave length of interest is 100 µm for obtaining coherent synchrotron radiation, so the reflectivity of a mirror is about 99. 45. Gold coated mirrors are very good to use in the infrared and we chose to use gold coated mirrors in the real time interferometer (RTI) experiment.…”
Section: Mirrorsmentioning
confidence: 99%
“…reflectivty and the SR power is expected to be less by about 7% because fourteen mirrors are used. According to [45], different metal coated mirrors were tested and compared. It was found that gold, silver, and aluminum coatings perform equally in the THz regime, so there is no reason to change the mirrors in order to decrease the loss from the mirrors.…”
Section: Mirror Reflectivitymentioning
confidence: 99%
“…Metallic mirrors are known to be achromatic and to show a very high efficiency, as actual metals in the THz range behave almost as ideal conductors [3]. Nevertheless, reflecting and focusing the mirrors are very sensitive to any misalignment and they do not work properly off the axis.…”
Section: Introductionmentioning
confidence: 99%